The Role of Educational Supervisors in Developinging the Professional Performance of Social Studies Teachers in Jordan From a Teacher’s Perspective - Mestarihi, Maha Mohammad (European Scientific Journal, ESJ, 2020)
This study aims to identify the role of the educational supervisors in developing the professional performance of social studies teachers in Jordan from a teacher’s perspective in the Irbid Governorate of Jordan by identifying the effect of (gender, academic qualification, school level, and years of experience) variables during the academic year 2019/2020. The study used a descriptive and analytical approach on a sample consisted of (120) social studies teachers (60 teachers from each gender) selected randomly from a population of (690) teachers distributed over (487) government schools. A researcher-made questionnaire with (35) response-close questions divided into five areas: planning, teaching methods, relationship with colleagues and the local community, classroom visits, and evaluation on the five-point Likert scale was used as a measuring instrument, and its validity and stability were confirmed. The results showed that both genders agree that there is a major role for educational supervisors in developing the professional performance of social studies teachers, and there is a statistically significant impact at the level of significance (α≥0.05) attributable to gender variable in the areas of planning and teaching methods in favor of females. As well as, there is a statistically significant impact at the level of significance (α≥0.05) attributable to academic qualifications variable in the areas of planning and teaching methods in favor of postgraduate degree holders. The results also showed that there is an effective role of the educational supervisor in developing the professional performance of social studies teachers from teachers’ perspective in Irbid Governorate of Jordan in the field of planning, relationship with colleagues and the local community in favor of primary schools, and no statistically significant impact of class visits, teaching methods and evaluation attributable to the school level variable. Also, there is a statistically significant impact at the level of significance (α≥0.05) attributable to years of experience in planning, teaching methods, and the relationship with colleagues and the local community in favor of the category (more than 10 years) of experience, and no statistically impact of classroom visits and evaluation attributed to years of experience variable. In light of the results, the main recommendation was that, that there is a necessity for reviewing the supervision system by the Ministry of Education to reinforce the educational supervision system and increase the quality of education, thus, a new educational supervision model based on multiple data sources based on guidance should be developed and rapidly adapted to compete with the rapid changes occurring in the educational system, as well, technological and educational changes.